A high temperature resistant cementing material and its preparation method and application
By using raw materials such as aluminate cement, fly ash and phosphate, combined with admixtures, a high temperature resistant cementing material was prepared, which solved the problem that the silicate cement system in the existing technology could not meet the engineering needs under the high temperature environment of 650℃, and achieved high compressive strength and good elastic modulus under the high temperature conditions of 650℃, which was suitable for cementing of shale oil in situ conversion wells.
Patent Information
- Application Number
- CN202310242091.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-14
AI Technical Summary
In the prior art, the silicate cement system cannot meet engineering needs under a high temperature environment of 650℃, and the strength and permeability data of the aluminate cement system at a high temperature of 650℃ are missing, and the strength decay and permeability increase of aluminate cement stone at a high temperature of 650℃ are not considered.
Aluminate cement is used as the main raw material, combined with fly ash and phosphate, and an appropriate amount of admixture is added to prepare a high-temperature cementing material through a specific preparation and maintenance process. The material can maintain good compressive strength and elastic modulus under high temperature conditions of 650°C, and control permeability below 0.7mD.
The high-temperature cementing material is under a high temperature environment of 650℃. The compressive strength of cement stone is not less than 31.5MPa and the elastic modulus is not less than 5.1GPa. It is suitable for cementing processes of low-maturity shale oil in situ conversion wells and hot production wells of ignition oil layer.
Smart Images

Figure CN116283164B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas well cementing, and specifically relates to a high-temperature resistant cementing material and a preparation method and application thereof. Background Art
[0002] my country's exploration and development of oil and gas resources has gradually transitioned from conventional oil and gas resources to unconventional oil and gas resources, including heavy oil, tight oil, and low-maturity shale oil. These unconventional oil and gas resources have the characteristics of poor fluidity and are difficult to exploit. For these unconventional resources with poor fluidity or low maturity, they are generally pre-treated by injecting high-temperature and high-pressure steam into the well or heating them in situ. After the unconventional oil is converted into oil and gas resources with better fluidity, it can be successfully exploited. When injecting high-temperature steam or heating in situ into the well, excessive temperature will cause the cement sheath to have reduced compressive strength and increased permeability. Therefore, in order to ensure the quality of cementing and realize the effective exploitation of unconventional oil and gas resources, the selection and optimization design of the cement slurry system are crucial.
[0003] The in-situ conversion of low-maturity shale oil in the prior art, such as the patent publication number CN110005390B, discloses that the complete pyrolysis temperature of low-maturity shale oil is 450-650°C.
[0004] The existing fire-burned oil layer cementing system, such as the cementing slurry system disclosed in the patent publication number CN105018056B, can meet the high temperature condition of 600° C. without strength decay.
[0005] The existing fire oil layer cementing system, such as the cementing slurry system disclosed in the patent publication number CN107721221A, can meet the high temperature condition of 600° C. without strength decay.
[0006] At present, there are few studies on cementing cement for low-maturity shale oil in-situ conversion wells, and the focus is mainly on the physical and mechanical properties of silicate cement under different high-temperature environments (Li Hailong et al., Physical and Mechanical Performance of Oil Well Cement Systems Under Simulated Shale Oil In-Situ Conversion Condition, 56th US Rock Mechanics / Geomechanics Symposium. One Petro, 2022.). Studies have shown that the compressive strength and elastic modulus of silicate cement both decline significantly between 550°C and 650°C, and the stress-strain behavior of cement stone changes from elastic to plastic. This phenomenon may be related to the decomposition of calcium carbonate in cement hydration products. Although the study also showed that adding silica sand to silicates can alleviate this phenomenon, the sand-modified cement stone after high-temperature treatment at 650°C still cannot meet engineering requirements.
[0007] Through the above analysis, the problems and defects of the prior art are as follows:
[0008] (1) The silicate cement system cannot meet engineering requirements under high temperature environment of 650℃.
[0009] (2) There is a lack of strength and permeability data for the existing aluminate cement system under high temperature conditions of 650°C.
[0010] (3) The existing technology does not take into account the problems of strength decay and increased permeability of aluminate cement paste under high temperature conditions of 650°C.
[0011] (4) The existing technology does not consider the stability of the elastic modulus of aluminate cement paste.
[0012] Therefore, silicate cement stone cannot meet the actual requirements of the project, and it is urgent to develop new cementing system materials. Summary of the invention
[0013] In view of the problems existing in the prior art, the present invention provides a high temperature resistant cementing material and its preparation method and application. After being exposed to 650°C for 7 days, the cement stone has good stability and compressive strength, and is suitable for shale oil in-situ conversion wells and thermal recovery wells of fire-burned oil layers.
[0014] The high temperature resistant cementing material of the present invention comprises, by weight, 100 parts of aluminate cement, 0-20 parts of fly ash, 2-5 parts of phosphate, 36-42 parts of water and 6 parts of admixture.
[0015] The admixture specifically includes 1 part of dispersant, 4 parts of fluid loss reducer and 1 part of defoamer.
[0016] The aluminate cement has a calcium oxide content of 45-50wt%, an aluminum oxide content of 38-40wt%, preferably, a calcium oxide content of 47wt%, and an aluminum oxide content of 39wt%; the aluminate cement particle size D50 is 17.22μm. It was purchased from Zhengzhou Jianai Special Aluminate Co., Ltd.
[0017] The fly ash described in the present invention is fine ash collected from the flue gas after coal combustion. It is the main solid waste produced by coal-fired power plants, and its main components are Al2O3, CaO, Fe2O3 and SiO2. Fly ash contains amorphous SiO2, which can promote the reaction between aluminate cement and water to form more stable chemical substances. Specifically, the silicon dioxide content in the fly ash is 58-61wt%, the aluminum oxide content is 17-19wt%, and the calcium oxide content is 6-8wt%. Preferably, the silicon dioxide content is 61wt%, the aluminum oxide content is 19wt%, and the calcium oxide content is 8wt%; the particle size D50 of the fly ash is 3.07μm.
[0018] The phosphate described in the present invention is sodium hexametaphosphate.
[0019] When fly ash is not used, the method for preparing the high temperature resistant cementing material comprises the following steps:
[0020] S1-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0021] S1-2: Cement paste I is cured at 45-55°C for 6-7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0022] When fly ash is used, the method for preparing the high temperature resistant cementing material comprises the following steps:
[0023] S2-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0024] S2-2 slowly adding fly ash to the cement slurry at a rotation speed of 3000-4000 rpm to obtain cement slurry II;
[0025] S2-3 Cement slurry II is cured at 45-55°C for 6-7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0026] The high temperature resistant cementing material of the present invention can be applied to the cementing process of low-maturity shale oil in-situ conversion wells.
[0027] The aluminate cement stone of the present invention is cured at 50° C. The addition of sodium hexametaphosphate not only promotes the flowability of cement slurry, but also inhibits the strength decay problem of cement stone.
[0028] The fly ash used in the present invention plays the role of an active additive, and contains a large amount of active silica in its composition, which can react with aluminate cement to improve the stability of aluminate cement. After adding fly ash, hydrated calcium aluminum feldspar is generated in the hydration product, which inhibits the strength decay under low temperature environment and also improves the strength under low temperature. When it is cured at low temperature, hydration products hexahydrate tricalcium aluminum, aluminum gel phase and aluminum feldspar are formed; when it is applied to the cementing process of low-maturity shale oil in-situ conversion wells, under a high temperature environment of 650°C, the hydration products hexahydrate tricalcium aluminum and aluminum gel are dehydrated to generate heptaaluminate dodecalcium and monocalcium aluminate with high crystallinity, good temperature resistance and crystal structure, and the hydrated calcium aluminum feldspar is dehydrated to become aluminum feldspar with good stability, so that the cement stone can withstand the high temperature of 650°C, and ensure that the compressive strength is not less than 31.5MPa and the elastic modulus is not less than 5.1GPa after 7 days of high temperature treatment at 650°C, which is suitable for the cementing process of low-maturity shale oil in-situ conversion wells.
[0029] The present invention has the following beneficial effects:
[0030] 1. Since the in-situ conversion and exploitation of low-maturity shale oil is still in the trial production stage, the cementing environment is novel, and there is little research on cementing cement for in-situ conversion wells of low-maturity shale oil. The cementing material of the present invention can withstand a high temperature of 650°C, and ensures that the compressive strength is not less than 31.5MPa and the elastic modulus is not less than 5.1GPa after 7 days of high-temperature treatment at 650°C, and is suitable for large-scale promotion and application.
[0031] 2. The change in the permeability of the cement sheath affects the production efficiency. If the permeability of the cement stone is large after being treated in a high-temperature environment, the oil and gas resources will escape to other formations during the production stage, reducing the production efficiency. The permeability of the cementing material described in the present invention is maintained below 0.7 mD. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of compressive strength test results of the cement system provided in an embodiment of the present invention.
[0033] Figure 2 A schematic diagram of elastic modulus test results of a cement system provided in an embodiment of the present invention.
[0034] Figure 3 A schematic diagram of the gas permeability test results of the cement system provided in an embodiment of the present invention.
[0035] Figure 4A schematic diagram of the XRD diffraction pattern of the cement system provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] The present invention is further described below in conjunction with comparative examples and test results. In the following specific examples, the operations involved, if the conditions are not specified, are carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials used without indicating the manufacturer and specifications can all be commercially available. Aluminate cement was purchased from Zhengzhou Jianai Special Aluminate Co., Ltd., with the trade name A700; sodium hexametaphosphate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; fluid loss reducer and defoamer were both from Sinopec Boxing Company, of which the fluid loss reducer model was BXF-200L and the defoamer model was G603.
[0038] Example 1
[0039] The present embodiment provides a high temperature resistant cementing material. The raw material composition of the cementing material is as follows, by weight: 100 parts of aluminate cement, 2 parts of sodium hexametaphosphate, 1 part of dispersant, 37 parts of water, 4 parts of fluid loss reducer, and 1 part of defoamer;
[0040] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0041] S1-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0042] S1-2 Cement paste I was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0043] The cement paste was cured for 7 days at 650° C. (simulating the heating conditions for in-situ conversion of low-maturity shale oil, the same below) and tested. The results are shown in Table 1.
[0044] Table 1 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0045] ;
[0046] As can be seen from Table 1, after curing at 50°C for 7 days, the compressive strength of the cement paste in Example 1 is 23.5 MPa and the elastic modulus is 12.4 GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Example 1 is 41.9 MPa, the elastic modulus is 6.9 GPa, and the permeability is 0.33 mD. Therefore, the cement paste in Example 1 can ensure a compressive strength of 41.9 MPa under the conditions of shale oil in-situ conversion (the maximum downhole heating temperature can reach 650°C), thereby ensuring the stability of low-maturity shale oil in the in-situ conversion process.
[0047] Example 2
[0048] The present embodiment provides a high temperature resistant cementing material, wherein the raw materials are composed of: 100 parts of aluminate cement, 10 parts of fly ash, 2 parts of sodium hexametaphosphate, 1 part of dispersant, 40 parts of water, 4 parts of fluid loss reducer, and 1 part of defoamer, in parts by weight;
[0049] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0050] S2-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0051] S2-2 slowly adding fly ash into the cement slurry at a rotation speed of 3500 rpm to obtain cement slurry II;
[0052] S2-3 Cement slurry II was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0053] The cement paste was cured at 650° C. for 7 days and tested. The results are shown in Table 2.
[0054] Table 2 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0055] ;
[0056] As can be seen from Table 2, after curing at 50°C for 7 days, the compressive strength of the cement paste in Example 2 is 37.2MPa and the elastic modulus is 13.6GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Example 2 is 51.4MPa, the elastic modulus is 10.2GPa, and the permeability is 0.93mD. Therefore, the cement paste in Example 2 can ensure a compressive strength of 51.4MPa under the conditions of shale oil in-situ conversion (the maximum downhole heating temperature can reach 650°C), thereby ensuring the stability of low-maturity shale oil in the in-situ conversion process.
[0057] Example 3
[0058] The present embodiment provides a high temperature resistant cementing material, wherein the raw materials are composed of: 100 parts of aluminate cement, 20 parts of fly ash, 2 parts of sodium hexametaphosphate, 1 part of dispersant, 42 parts of water, 4 parts of fluid loss reducer, and 1 part of defoamer, in parts by weight;
[0059] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0060] S2-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0061] S2-2 slowly adding fly ash into the cement slurry at a rotation speed of 3500 rpm to obtain cement slurry II;
[0062] S2-3 Cement slurry II was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0063] The cement paste was cured at 650° C. for 7 days and tested. The results are shown in Table 3.
[0064] Table 3 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0065] ;
[0066] As can be seen from Table 3, after curing at 50°C for 7 days, the compressive strength of the cement paste in Example 3 is 25.9 MPa and the elastic modulus is 11 GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Example 3 is 49.1 MPa, the elastic modulus is 9.1 GPa, and the permeability is 0.35 mD. Therefore, the cement paste in Example 3 can ensure a compressive strength of 49.1 MPa under the conditions of shale oil in-situ conversion (the maximum downhole heating temperature can reach 650°C), thereby ensuring the stability of low-maturity shale oil in the in-situ conversion process.
[0067] Example 4
[0068] The present embodiment provides a high temperature resistant cementing material, wherein the raw materials are composed of: 100 parts of aluminate cement, 5 parts of sodium hexametaphosphate, 1 part of dispersant, 37 parts of water, 4 parts of fluid loss reducer, and 1 part of defoamer, in parts by weight;
[0069] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0070] S1-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0071] S1-2 Cement paste I was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0072] The cement paste was cured at 650° C. for 7 days and tested. The results are shown in Table 4.
[0073] Table 4 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0074] ;
[0075] As can be seen from Table 4, after curing at 50°C for 7 days, the compressive strength of the cement paste in Example 4 is 22.4 MPa and the elastic modulus is 9.4 GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Example 4 is 47.2 MPa, the elastic modulus is 6.1 GPa, and the permeability is 0.77 mD. Therefore, the cement paste in Example 4 can ensure a compressive strength of 47.2 MPa under the conditions of shale oil in-situ conversion (the maximum downhole heating temperature can reach 650°C), thereby ensuring the stability of low-maturity shale oil in the in-situ conversion process.
[0076] Example 5
[0077] The present embodiment provides a high temperature resistant cementing material, wherein the raw materials are composed of: 100 parts of aluminate cement, 10 parts of fly ash, 5 parts of sodium hexametaphosphate, 1 part of dispersant, 39 parts of water, 4 parts of fluid loss reducer, and 1 part of defoamer, in parts by weight;
[0078] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0079] S2-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0080] S2-2 slowly adding fly ash into the cement slurry at a rotation speed of 3500 rpm to obtain cement slurry II;
[0081] S2-3 Cement slurry II was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0082] The cement paste was cured at 650° C. for 7 days and tested. The results are shown in Table 5.
[0083] Table 5 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0084] ;
[0085] As can be seen from Table 5, after curing at 50°C for 7 days, the compressive strength of the cement paste in Example 5 was 18.2 MPa and the elastic modulus was 7.7 GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Example 5 was 36.4 MPa, the elastic modulus was 5.1 GPa, and the permeability was 0.42 mD. Therefore, the cement paste in Example 5 can ensure a compressive strength of 36.4 MPa under the conditions of shale oil in-situ conversion (the maximum downhole heating temperature can reach 650°C), thereby ensuring the stability of low-maturity shale oil in the in-situ conversion process.
[0086] Example 6
[0087] The present embodiment provides a high temperature resistant cementing material, wherein the raw materials are composed of: 100 parts of aluminate cement, 20 parts of fly ash, 5 parts of sodium hexametaphosphate, 1 part of dispersant, 42 parts of water, 4 parts of fluid loss reducer, and 1 part of defoamer, in parts by weight;
[0088] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0089] S2-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I;
[0090] S2-2 slowly adding fly ash into the cement slurry at a rotation speed of 3500 rpm to obtain cement slurry II;
[0091] S2-3 Cement slurry II was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0092] The cement paste was cured at 650° C. for 7 days and tested. The results are shown in Table 6.
[0093] Table 6 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0094] ;
[0095] As can be seen from Table 6, after curing at 50°C for 7 days, the compressive strength of the cement paste in Example 6 is 16.1 MPa and the elastic modulus is 4.8 GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Example 6 is 31.5 MPa, the elastic modulus is 5.2 GPa, and the permeability is 0.37 mD. Therefore, the cement paste in Example 6 can ensure a compressive strength of 31.5 MPa under the conditions of shale oil in-situ conversion (the maximum downhole heating temperature can reach 650°C), thereby ensuring the stability of low-maturity shale oil in the in-situ conversion process.
[0096] Comparative Example 1
[0097] This comparative example provides a high temperature resistant cementing material, which is composed of the following raw materials in parts by weight: 100 parts of aluminate cement, 1 part of dispersant, 36 parts of water, 4 parts of fluid loss reducer, and 1 part of defoamer;
[0098] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0099] S1-1 aluminate cement, water and admixture are prepared in proportion to obtain cement slurry I;
[0100] S1-2 Cement paste I was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0101] The cement paste was cured at 650°C for 7 days and tested. The results are shown in Table 7.
[0102] Table 7 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0103] ;
[0104] It can be seen from Table 7 that after curing at 50°C for 7 days, the compressive strength of the cement paste in Comparative Example 1 is 20.4 MPa and the elastic modulus is 12.1 GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Comparative Example 1 is 33.2 MPa, the elastic modulus is 3.6 GPa, and the permeability is 1.1 mD.
[0105] Comparative Example 2
[0106] This comparative example provides a high temperature resistant cementing material, which is composed of the following raw materials in parts by weight: 100 parts of silicate cement, 2 parts of dispersant, 41 parts of water, 4 parts of fluid loss reducer, and 0.5 parts of defoamer;
[0107] The preparation method of the high temperature resistant cementing material comprises the following steps:
[0108] S1: preparing silicate cement, water and admixture according to proportion to obtain cement slurry I;
[0109] S1-2 Cement paste I was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
[0110] The cement paste was cured at 650° C. for 7 days and tested. The results are shown in Table 8.
[0111] Table 8 Comparison of compressive strength, elastic modulus and permeability of high temperature resistant aluminate cement paste
[0112] ;
[0113] It can be seen from Table 8 that after curing at 50°C for 7 days, the compressive strength of the cement paste in Comparative Example 2 is 50.0 MPa and the elastic modulus is 14.0 GPa. After high-temperature curing at 650°C for 7 days, the compressive strength of the cement paste in Comparative Example 2 is 6.2 MPa, the elastic modulus is 1.0 GPa, and the permeability is 7.6 mD.
[0114] The cementing systems of Examples 1 to 6 and Comparative Examples 1 and 2 were cured at 50°C and 650°C for 7 days, and the compressive strength and elastic modulus of each example were compared. The results are as follows: Figure 1 and Figure 1 As shown. Figure 1 It can be seen that the compressive strength of the cement paste in Example 2 before and after high temperature is significantly higher than that of other formulations. All the embodiment formulations are cured at 650°C for 7 days, and the compressive strength is higher than 31.5MPa. Figure 2 It can be seen that the elastic modulus of the cement paste in Example 2 is significantly higher than that of other formulations. All the example formulations are cured at a high temperature of 650°C for 7 days, and the elastic modulus is higher than 5 GPa. Figure 3 The permeability results of high temperature resistant aluminate cement stone after curing at 650°C for 7 days show that the permeability values in Comparative Examples 1 and 2 are significantly higher than those in other embodiments, indicating that the embodiments of the present technical solution can reduce the permeability of cement stone to a certain extent. Figure 4 The XRD diffraction pattern results of various embodiments and comparative examples show that the diffraction pattern does not change much with the formula, but with the increase of fly ash content, the peak value of dodecaluminate heptaaluminate (about 33°) shows a downward trend.
[0115] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant cementing material suitable for cementing low-maturity shale oil in-situ conversion wells, characterized in that: In parts by weight, the raw materials are composed of: 100 parts of aluminate cement, 10 parts of fly ash, 2 parts of sodium hexametaphosphate, 6 parts of admixtures, and 40 parts of water; the admixtures are 1 part of dispersant, 4 parts of fluid loss reducer, and 1 part of defoamer; The fly ash has a silicon dioxide content of 58-61wt%, an aluminum oxide content of 17-19wt%, and a calcium oxide content of 6-8wt%; the particle size D50 of the fly ash is 3.07μm; The specific steps are: S2-1 aluminate cement, phosphate, water and admixture are prepared in proportion to obtain cement slurry I; S2-2 slowly adding fly ash into the cement slurry at a rotation speed of 3500 rpm to obtain cement slurry II; S2-3 Cement slurry II was cured at 50°C for 7 days to obtain cement paste, i.e., high temperature resistant cementing material.
2. The method for preparing a high temperature resistant cementing material suitable for cementing of low-maturity shale oil in-situ conversion wells according to claim 1, characterized in that: The calcium oxide content of the aluminate cement is 45-50wt%, and the aluminum oxide content is 38-40wt%; the particle size D50 of the aluminate cement is 17.22μm.
Citation Information
Patent Citations
Cementing system for oil formation in flames
CN105018056B
Methods for in-situ conversion and extraction of shale oil and gas from large wells in medium- and low-maturity shale oil fields
CN110005390B
High-temperature-resistant phosphate cement and application thereof
CN107721221A